2008
DOI: 10.1086/592304
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Single‐Nucleotide Polymorphism in the Pregnane X Receptor (PXR63396C→T) with Reduced Concentrations of Unboosted Atazanavir

Abstract: This study investigated pregnane X receptor polymorphisms in relation to unboosted atazanavir plasma concentrations in 2 cohorts of patients. The polymorphism 63396T-->C predicted concentrations below the minimum effective concentration (150 ng/mL) with odds ratios of 18 (P = .008) and 5.13 (P = .02). Prospective studies determining potential clinical usefulness are now warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 17 publications
2
43
2
Order By: Relevance
“…Indeed, the amount of PXR induction that occurs due to the administration of rifampin was shown to be inversely proportional to the baseline PXR activity (12). The trend that we observed of increased CL/F values for PXR C63396T carriers is, however, consistent with the decrease in atazanavir plasma concentrations found for individuals with this polymorphism (22). High levels of P-glycoprotein activity may limit the distribution of rifampin in the body, leading to lower V/F values and higher plasma concentrations, as was previously suggested for digoxin (19).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the amount of PXR induction that occurs due to the administration of rifampin was shown to be inversely proportional to the baseline PXR activity (12). The trend that we observed of increased CL/F values for PXR C63396T carriers is, however, consistent with the decrease in atazanavir plasma concentrations found for individuals with this polymorphism (22). High levels of P-glycoprotein activity may limit the distribution of rifampin in the body, leading to lower V/F values and higher plasma concentrations, as was previously suggested for digoxin (19).…”
Section: Discussionsupporting
confidence: 82%
“…We recently found that homozygosity of 63396C3T is associated with suboptimal ATV C trough (36) in patients receiving an unboosted regimen. Identifying sources of pharmacokinetic variability is important for clinical management and may aid optimal dose selection.…”
mentioning
confidence: 99%
“…The most studied polymorphism at NR1I2 is the 63396C>T, which has been associated with an increased activity of CYP3A4, leading to variations in ATV exposure. In this regard, homozygosity for the NR1I2-63396-T genotype is a predictor for sub-therapeutic ATV levels [53,54].…”
Section: Pharmacogenetics Of Atazanavirmentioning
confidence: 99%
“…In a study conducted by Siccardi et al [53], a score based in 3 SNPs, ABCB1 (3435C>T), SLCO1B1 (521T>C) and PXR (63396C>T), was proposed as the best predictor of unboosted ATV plasma exposure in the clinical setting [55]. The pharmacogenetic score was calculated as the sum of favourable genotypes.…”
Section: Pharmacogenetics Of Atazanavirmentioning
confidence: 99%